2020
DOI: 10.1021/acs.macromol.0c00962
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synchrotron Radiation X-ray Scattering Investigation of a Microphase-Separated Structure of Thermoplastic Elastomers under Uniaxial and Equi-Biaxial Deformation Modes

Abstract: Changes in the microphase-separated structure of the poly­(styrene-b-ethylene-co-butylene-b-styrene) (SEBS) triblock copolymer (13 wt % polystyrene (PS) block) were investigated during mechanical deformation. In situ synchrotron radiation small-angle X-ray scattering (SAXS)/wide-angle X-ray scattering (WAXS) measurements were successfully performed for SEBS under equi-biaxial deformation as well as under uniaxial deformation. In situ SAXS/WAXS measurements revealed changes in (1) the shape of spherical PS doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Recently, scattering coupled with in situ rheological measurements has become more popular to aid in the development of structure–property relationships. Rheo-small-angle-neutron scattering (rheo-SANS, Figure ) is most common in polymer networks due to the contrast selectivity as mentioned for static SANS, and it provides a direct correlation between the structure and the macroscopic rheological response. There are a number of flow devices compatible with in situ neutron scattering measurements (flow-SANS or rheo-SANS), most notably, Couette cells, capillary flow cells, 1–2 shear cells, and even entire oscillatory rheometers .…”
Section: Network Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, scattering coupled with in situ rheological measurements has become more popular to aid in the development of structure–property relationships. Rheo-small-angle-neutron scattering (rheo-SANS, Figure ) is most common in polymer networks due to the contrast selectivity as mentioned for static SANS, and it provides a direct correlation between the structure and the macroscopic rheological response. There are a number of flow devices compatible with in situ neutron scattering measurements (flow-SANS or rheo-SANS), most notably, Couette cells, capillary flow cells, 1–2 shear cells, and even entire oscillatory rheometers .…”
Section: Network Structurementioning
confidence: 99%
“…Capillary and microfluidic flow devices, , for low sample volume experiments under arbitrary deformation fields, are also available. Such rheo-SANS experiments have given insights into the interplay of chain branching and alignment with the formation/breakage of reversible cross-links under different shear conditions. Further, rheo-SAXS has shown that the glassy styrene domains (within a microphase-separated poly­(styrene- b -ethylene- co -butylene- b -styrene) (SEBS) triblock thermoplastic elastomer) change shape, spacing, and ordering while undergoing uniaxial or biaxial stretching …”
Section: Network Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of multiaxial deformation, such as biaxial, [13][14][15][16][17][18][19][20] compression, 21 bulge, 22 lateral indentation, 23 and flow, 24 in terms of understanding the physical properties of polymers is well known. This is because (1) the polymers have a string-shaped structure, (2) they can become entangled, and (3) the strain density energy function of the materials can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…For a precise and deep understanding of the behavior of transient networks, in situ observations of the internal structure of specimens under deformation are important. For elastomers and gels, in situ small-angle X-ray scattering (SAXS) is frequently employed. ,, For example, Winey et al observed the morphological changes in precise acid polyethylenes and their metal-neutralized ones using in situ SAXS with stretching. Sakurai et al reported the deformation of a glassy polystyrene spherical domain in a polystyrene- block -poly­(ethylene- co -butylene)- block -polystyrene elastomer with uniaxial stretching . Kojio et al investigated the deformation behavior of polythiouretane elastomers using the combination of in situ SAXS, in situ wide-angle X-ray scattering (WAXS), and in situ X-ray absorption fine structure methods with stretching .…”
Section: Introductionmentioning
confidence: 99%